El editorial en la prensa mexicana - Navarro Zamora, Lizy (Estudios sobre el Mensaje Periodístico, 2007)
Mexican Press does not fulfill its role of guiding the national and international issues that are most important. 6 out of 15 national major newspapers, publish the editorial where they establish their opinions. The newspapers which do not include editorial, diminish the importance of it, taking in consideration that the free expression presented in this genere enriches the whole democratic society.